Upaya Diaspora Indonesia Di Amerika Serikat Dalam Meningkatkan Brand Awardness Melalui Food Festival - Aucky Adi Kurniawan, Nurdiana Abhiyoga Hartoni (Mandala: Jurnal Ilmu Hubungan Internasional, 2019)
Public diplomacy is one way to enhance inter-state cooperation through non-state actors. Among them is gastro diplomacy which is part of public diplomacy to realize the ideals of the two countries. Gastro diplomacy is food diplomacy to enhance Indonesia's brand awareness. The Indonesian Culinary Festival held in New York by the Embassy of the Republic of Indonesia is a tangible proof of a major activity to increase the country's cultural-tourism consumers, the Indonesian Diaspora coffers in the United States are actors who play an active role in this festival. Indonesian traditional food is part of an increase in Indonesia's tourism economy in the hope of increasing international interaction and cooperation. This paper will analyze the concepts, practices, and cons regarding gastro diplomacy. Starting from nation branding, this paper is expected to provide an overview of the concept of gastro diplomacy.